2019
DOI: 10.26434/chemrxiv.9745289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Design Realizing Very Fast Reverse Intersystem Crossing in Purely Organic Emitter

Abstract: Reverse intersystem crossing (RISC), originally considered forbidden in purely organic materials, has been recently enabled by minimizing the energy gap between the lowest singlet excited state (S<sub>1</sub>) and lowest triplet state (T<sub>1</sub>) in thermally activated delayed fluorescence (TADF) systems. However, direct spin-inversion between S<sub>1</sub> and T<sub>1</sub> is still inefficient when both states are of the same charge transfer (CT) nature (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, k RISC of over 10 7 s -1 for Br-3-PXZ-XO is the highest value ever reported for an organic TADF material 28 . This high k RISC reflects its fast transient photoluminescence decay with a delayed fluorescence lifetime of 490 ns (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…To the best of our knowledge, k RISC of over 10 7 s -1 for Br-3-PXZ-XO is the highest value ever reported for an organic TADF material 28 . This high k RISC reflects its fast transient photoluminescence decay with a delayed fluorescence lifetime of 490 ns (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Kaji and co-workers 49 recently reported a through-space CT molecule, TpAT-tFFO, by introducing face-to-face alignment of the donor and acceptor units (Fig. 7a).…”
Section: Discussionmentioning
confidence: 99%
“…5). While the existing organic TADF molecules exhibit k RISC smaller than 10 8 s -1 , the theory predicts that even k RISC of 10 9 s -1 , corresponding to a time constant of 1.0 ns, can be achieved with H SO less than 10 cm -1 ; for example, H SO 10 of 7.7 cm -1 for E A of 0.10 eV and H SO of 2.9 cm -1 for E A of 0.05 eV at T of 300 K. These H SO are an order of magnitude smaller than those of iridium-containing phosphors and could be achieved by exploiting heavy atom effects of nonmetals in periods 3 and 4 30,31 . However, we have shown that such heuristic approaches sometimes lead to the retardation of H SO , in part because of their more pronounced effects on S1 S1-T2 difference T2 the excited-state electronic configurations at the S 1 -T 2 MESX geometries.…”
Section: Resultsmentioning
confidence: 99%